Optical and Structural Characterization of Pin Photodetector Based on Germanium Nanocrystals for Third Generation Solar Cells - K.K. Sossoe; M.M. Dzagli; K.S. Gadedjisso-Tossou; A.M. Mohou; B. Grandidier (Журнал нано- та електронної фізики)
We investigated the structural and optoelectronic properties of p-n germanium nanocrystals based junctions embedded between GaAs substrate and layers of ZnO:Al or a-Si:H. Scanning electron microscopy and scanning tunneling microscopy were used on these junctions in this work. Calculations of tunneling current on the substrate showed effect of localized defects trapping Fermi level at the surface tending to make a semi-insulating substrate. The average value of the diameter of the Ge nanoparticle is around 12.5 nm. These results lay the foundation for the development of solar cells which active part is made of GeNCs.